Addressing insecurity through good governance: A panacea for stable and peaceful Africa - Fatokun, Olalekan Samuel; Rotimi , Olajide Opeyeoluwa (Journal of Contemporary International Relations and Diplomacy, 2022)
The realization of a peaceful and stable Africa as one of the goals and aspirations of the ‘African Union Agenda 2063: the Africa We Want’ is achievable but only in an environment devoid of insecurity and other conditions that threaten human existence. The insecurity challenges in some parts of Africa have assumed a formidable dimension that requires a multi-stakeholder approach to resolve. Meanwhile, good governance has proved to be a virile mechanism to address insecurity and ameliorate conditions that threaten human existence. It is a major driving force towards peace, security, and sustainable development in any country of the world that has experienced or still experiencing such development. This study argues that a stable and peaceful Africa is a mirage in the face of insecurity that is prevalent in some parts of Africa and that good governance is the major antidote to address the issue of insecurity. This study employs content analysis as a source of data collection and engages descriptive research design in its analysis.